The Geotourism Development Strategies for Khon Kean Geopark Towards to UNESCO Global Geopark - Jantakham, Supamitr; Sairaksa, Danwichai; Singhalert, Rungsan (Journal of Education Rajabhat Maha Sarakham University, 2020)
The purposes of this research were to develop and evaluate geotourism strategies for Khon Kaen Geopark towards to UNESCO Global Geopark through research operated using mixed methodologies with qualitative of conducting strategies plan, collected form In-depth interviews, brainstorming and focus group with Khon Kean Geopark Committee totally were 55 personal through used SWOT analysis and TOWS matrix and quantitative of the evaluation of suitability and possibility format for the strategies with 9 experts in field of geoparks and geotourism in national and global level. The data were analyzed using descriptive statistics was mean and standard deviation. The research revealed that the strategies-made conducted had a vision was Khon Kaen Geopark was a tourism park and dinosaur learning center towards Global Geopark consist of 5 missions, 5 objectives, 5 strategic issues, 11 goals, 22 strategies, 34 indicators, and 78 projects. Five strategic issues included (1) participatory conservation and protection of geological heritage resources, (2) Geopark holistic management towards global network, (3) upgrading Khon Kaen Geopark to become UNESCO Global Geopark for dinosaur and local wisdom tourism, (4) promoting education and communication for geotourism through innovation and (5) sustainable local economy development. And the results of evaluating the developed strategies for the geotourism development of Khon Kaen Geopark towards to UNESCO Global Geopark showed that overall suitable ( = 4.54, S.D. = .569) of the developed strategies were at a highest level and feasible implementation ( = 4.50, S.D. = .591) of the developed strategies were at a high level.